下面公式是合取范式的有()
A: p
B: ¬p
C: p∨¬q
D: p∨¬q∨
E: p∧¬q
F: (p∧¬q)∨
G: (p∧¬q)∨r∨(p→r)
H: ¬(p∧¬q)∨
I: p∧(q∨r)
J: (p∨¬r)∧(¬q∨r)∧(¬p∨q∨r)
A: p
B: ¬p
C: p∨¬q
D: p∨¬q∨
E: p∧¬q
F: (p∧¬q)∨
G: (p∧¬q)∨r∨(p→r)
H: ¬(p∧¬q)∨
I: p∧(q∨r)
J: (p∨¬r)∧(¬q∨r)∧(¬p∨q∨r)
举一反三
- 计算(¬P → Q)←→ R主析取范式规范正确的是 ——————— 。 A: (P ∧ Q ∧ ¬R) ∨ (P ∧ ¬Q ∧ R) ∨ (¬P ∧ Q ∧ R) ∨ ( ¬P ∧ ¬Q ∧ R) B: (P ∧ Q ∧ ¬R) ∨ (P ∧ ¬Q ∧ R) ∨ (¬P ∧ Q ∧ R) ∨ ( ¬P ∧ ¬Q ∧ R) C: ( P ∧ Q ∧ R)∨ (P ∧ ¬Q ∧ R)∨ (¬P ∧ Q ∧ R) ∨ (¬P ∧ ¬Q ∧ ¬R) D: (¬P ∧ ¬Q ∧ ¬R) ∨ (¬P ∧ Q ∧ R) ∨ (P ∧ ¬Q ∧ R) ∨ ( P ∧ Q ∧ R)
- 计算(P→Q)∧(¬P→R)的主析取范式规范正确的是 ——————— 。 A: (¬P ∧ R) ∨ (P ∧ Q) ∨ (Q ∧ R) B: (P ∧ Q ∧ R) ∨ (P ∧ Q ∧ ¬R) ∨ (¬P ∧ Q ∧ R) ∨ (¬P ∧ ¬Q ∧ R) C: (¬P ∧ ¬Q ∧ R) ∨ (¬P ∧ Q ∧ ¬R) ∨ (P ∧ Q ∧ ¬R) ∨ (P ∧ Q ∧ R) D: (¬P ∧ ¬Q ∧ R) ∨ (¬P ∧ Q ∧ R) ∨ (P ∧ Q ∧ ¬R) ∨ (P ∧ Q ∧ R)
- 计算(¬P → Q)←→ R析取范式规范正确的是 ——————— 。 A: (P ∧ ¬Q ∧ ¬R) ∨ (P ∧ R) ∨ ( Q ∧ R) B: (¬P ∧ ¬Q ∧ ¬R) ∨ (P ∧ R) ∨ ( Q ∧ R) C: (P ∧ ¬Q ∧ ¬R) ∨ (P ∧ Q) ∨ ( Q ∧ R) D: (P ∧ ¬Q ∧ ¬R) ∨ (¬P ∧ Q) ∨ ( Q ∧ R)
- 下面公式是合取范式的有() A: ¬p B: p∨¬q∨ C: ¬(p∧¬q)∨ D: (p∨¬r)∧(¬q∨r)∧(¬p∨q∨r)
- 下面公式是合取范式的有() A: ¬p B: (p∧¬q)∨ C: (p∧¬q)∨r∨(p→r) D: (p∨¬r)∧(¬q∨r)∧(¬p∨q∨r)